2016
DOI: 10.1111/pbr.12373
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of PCR‐based molecular markers to identify male‐sterile and maintainer plants from Indian onion (Allium cepa L.) populations

Abstract: The main aim of this study was to validate PCR markers for determining cytoplasm and genotypes at the Ms locus in short-day onion. Three cytoplasmic (OSN, MKFR and accD) and four nuclear (OPT, jnurf13, AcSKP1 and AcPMS1) markers were employed. Sel. 121-1 had 100% S cytoplasm, whereas Sel. 121-2, 'Pusa Red' and 'Pusa Madhavi' had 88%, 33% and 17% S cytoplasm, respectively. 'Early Grano' and 'Pusa Riddhi' did not possess S cytoplasm. Observations in 33 commercial varieties revealed two with sterile (S) cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…Despite the advance in the cytoplasmic identification, the identification of the 'B' line was dependent on manual backcrosses in the field. Identification of the cytoplasm type was performed by Ragassi et al (2010) and Santos et al (2012), in predominantly Brazilian germplasm, and by Khar and Saini (2016) in Indian germplasm. Huo et al (2015) and Kim et al (2015) reported the development of markers for identification of the male-sterility restorer nuclear locus (Ms) making it possible to fully identify 'A' and 'B' lines assisted by markers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advance in the cytoplasmic identification, the identification of the 'B' line was dependent on manual backcrosses in the field. Identification of the cytoplasm type was performed by Ragassi et al (2010) and Santos et al (2012), in predominantly Brazilian germplasm, and by Khar and Saini (2016) in Indian germplasm. Huo et al (2015) and Kim et al (2015) reported the development of markers for identification of the male-sterility restorer nuclear locus (Ms) making it possible to fully identify 'A' and 'B' lines assisted by markers.…”
Section: Introductionmentioning
confidence: 99%
“…The accD cytoplasmic marker together with the AcPms1 nuclear marker correctly predicted male sterility across all three populations, although not necessarily male fertility restoration. Although Khar and Saini (2016) observed that these markers were not completely accurate in germplasm from the Indian subcontinent, we can recommend their use for marker-aided selection of maintainer lines for onion populations of European or North American origins (Havey and von Kohn, 2017) toward the development of male sterile inbred lines for the production of onion hybrids. Means followed by the same letter in parentheses in columns and rows were not significantly different using Tukey's honestly significant difference test at P = 0.05.…”
Section: Resultsmentioning
confidence: 92%
“…), but their validation is needed before applying them in MAS of maintainer lines (Saini et al. , Khar and Saini ).…”
Section: Pollination Control Methods In Different Vegetable Cropsmentioning
confidence: 99%
“…Several molecular markers have been developed to identify the different cytoplasm types, thus reducing time and labour (Havey 1995, Sato 1998, Engelke et al 2003, Cho et al 2006, Kohn et al 2013. Likewise, many attempts have been made to develop molecular markers tightly linked to the Ms locus (G€ okc ße et al 2002, Bang et al 2011, Huo et al 2012, Yang et al 2013, Havey 2013, Huo et al 2015, Kim et al 2015, but their validation is needed before applying them in MAS of maintainer lines (Saini et al 2015, Khar andSaini 2016).…”
Section: Amaryllidaceaementioning
confidence: 99%